MEMBANGUN KURIKULUM PENDIDIKAN KARAKTER YANG HOLISTIK: INTEGRASI NILAI-NILAI MORAL DAN ETIKA DALAM SETIAP MATA PELAJARAN - Fahrezi, Muhammad Adnan; Nurwahid, Muhammad Salman; Baharuddin, Baharuddin (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
In Indonesia, creating a thorough character education curriculum is becoming more and more crucial due to the necessity to raise morally and intellectually upright youth. This article's goal is to demonstrate how moral and ethical principles can be applied to any topic to provide all-encompassing character education. Using a qualitative methodology, this study's literature reviews and in-depth interviews with Indonesian education specialists were carried out. Information was gathered from relevant journals, books, papers, and interviews. The findings of the study demonstrate that comprehensive character education needs to be implemented in all academic areas and encompass all facets of education. Experts concur that integrating moral and ethical principles into the curriculum can help pupils realise how important it is to have good moral character. Increasing students' moral awareness, ethical behaviour, and social interaction quality are among the key research outcomes. Results from this procedure are good in Indonesia. As a result, it's critical that educators and decision-makers keep pushing for the inclusion of moral and ethical principles in the curriculum.